2001
DOI: 10.1161/hc5001.102229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resynchronization Therapy Stimulation Site on the Systolic Function of Heart Failure Patients

Abstract: on behalf of the Pacing Therapy for Chronic Heart Failure II (PATH-CHF-II) Study Group Background-Cardiac resynchronization therapy (CRT) improves systolic function in heart failure patients with ventricular conduction delay by stimulating the left ventricle (LV) or both ventricles (biventricular, BV). Optimal LV site selection is of major clinical interest for CRT device implantation; however, the dependence of hemodynamics on LV stimulation site has not been established. Thus, the objective of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
314
2
14

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 586 publications
(352 citation statements)
references
References 12 publications
(10 reference statements)
19
314
2
14
Order By: Relevance
“…Early CRT studies showed that a lateral or posterolateral LV lead position was associated with a superior hemodynamic benefit than anterior positions 14. Other clinical studies, however, have not been consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Early CRT studies showed that a lateral or posterolateral LV lead position was associated with a superior hemodynamic benefit than anterior positions 14. Other clinical studies, however, have not been consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Butter et al compared the acute effects of LV pacing site (anterior vs. free wall) on net change in global systolic function. He found that LV free wall pacing consistently resulted in greater increases in dP/dtmax and aortic pulse pressure than did anterior pacing (35). Accordingly, CS pacing leads are typically placed in midlateral wall positions, frequently over a guideword directed into the selected tributary3.In a study by Gasparini et al the effects of differential pacing sites were evaluated in CRT treated patients, the results were not in favor of lateral wall pacing.…”
Section: Where To Pace; Bi -Ventricular or LV Anterior Or Free Wall?mentioning
confidence: 99%
“…Some authors stress the placement of left ventricle electrode into the lateral wall of the left ventricle, for reason of better hemodynamic response than other walls of the left ventricle 16 . Stimulation of the left ventricle anterior wall can lead to deterioration of cardiac failure and mitral regurgitation 17 .…”
Section: % Of Cases Does the Resynchronization Therapy Lead To Reducmentioning
confidence: 99%